An investigation of the role of Wasta social capital in enhancing employee loyalty and innovation in organizations - Arwa Al-Twal; Mohammad Alawamleh; Doaa M. F. Jarrar (Journal of Innovation and Entrepreneurship, 2024)
Considering the pressures of fluctuating external environments, organizations are constantly seeking ways to be responsive and able to improve their performance with lower costs. Employer-employee relationships have changed rapidly in recent years, and there is growing interest in considering human resources as a form of capital, and a strategic factor for business excellence. A focal point for HR professionals is employee loyalty, recognized as pivotal in realizing long-term organizational goals. This paper delves into the concept of Wasta social capital and its pivotal role in fostering employee loyalty and innovation within the unique cultural context of the Arab world. It is argued here that Wasta social capital is the fundamental dynamic that stimulates employee loyalty in the workplace. This conceptual paper provides new insights through understanding the significant role Wasta social capital plays in affecting employee loyalty in a collectivist culture, differing from the conventional business-context factors of loyalty. Obtaining a deeper understanding of employee loyalty and how it is developed in Arab-world business contexts can promote innovation.
Keywords: 650; Culture; Employee loyalty; Innovation; Middle East; Wasta social capital